Low level temperature profile from screen temperature (MAUSAM, 1979)
A simple mathematical model for vertical temperature profile during clear and calm night time inversions, utilising screen air temperature data is presented. The model was tested at Delhi and Mathura and found to be reasonably good for pollution studies in the absence of actual data.